Pengaruh Motivasi, Kompensasi dan Lingkungan Kerja Terhadap Kepuasan Kerja Karyawan (Studi Pada Perumda Tirta Mulia Kabupaten Pemalang) - Ismi Wijayanti, Yulia; Isnowati, Sri (Politeknik Piksi Ganesha Indonesia, 2024)
The potential of all employees influences the company's success in achieving its goals. The company will achieve its goals if employees work well, which depends on their level of satisfaction with their work. This research aims to analyze the influence of motivation, compensation and work environment on job satisfaction. The method used is a quantitative approach. The sampling technique in this research was to apply the saturated sampling method in determining the number of samples, namely 101 employees. The data collection technique was carried out by distributing questionnaires. The results of this research indicate that partially motivation, financing and work environment have a positive and significant effect on employee job satisfaction at Perumda Tirta Mulia, Pemalang Regency. The variables of motivation, compensation and work environment simultaneously have a significant effect on employee job satisfaction at Perumda Tirta Mulia, Pemalang Regency.